Childhood and its regimes of visibility in Brazil: An analysis of the contribution of the social sciences - de Castro, Lucia Rabello; Kosminsky, Ethel V. [UNESP] (SAGE Publications, 2010)
This article analyses the contribution of the social sciences to the visibility of children's issues in Brazilian society from the 1960s to the present day. The first regime of visibility considered childhood a relevant structural component of social inequalities, a 'social problem', stimulating social scientists to support social policies. Studies of children's labour and, most importantly, of educational issues stimulated a variety of research directions. The second regime of visibility disclosed the actor behind the child, revealing the child as a social actor and a subject of rights. Childhood studies gained impetus on account of new legislation following the internationalization of children's rights. Despite the broader scope of issues that social research on childhood has addressed, more sustained investment is needed so that childhood can attain a more equal position vis-a-vis other more salient research topics, and secure, de facto, the role of active participants in social life for children. © International Sociological Association.
Keywords: Brazil; Childhood; Children's rights; Social image; Social problem; Social sciences; Society; Visibility